موجبات عذاب بني إسرائيل في ضوء القرآن الكريم: Reason for the Torment of the Children of Israel in the light of the Noble Quran - Afshin Shafiq (Al Manhal Research Journal, 2023)
This topic is related to the interpretation of the Noble Quran which is the most honorable and best of sciences. God Almighty made this universe wonderful and created wonderful and useful creatures in it, among these creatures, man created the best and most honorable of creatures. The Quran has dealt with example of people who deserved God torment and wrath, and among these people are the children of Israel so that we can take a lesson from them, divine blessings are constantly pouring out on creatures, especially humans however God almighty has singled out the children of Israel from among the rest of the nations with special and outstanding care, And He completed the proof of them in this way, but they exchanged the blessing for disbelief and stubbornness. They directed the blessings of God with firmness, patient at times, and persistence in stubbornness in the wrong position and sometimes inappropriate situations, until they deserved divine punishment for their actions, from blasphemy to grace to worshiping desires and love of the world.